2020
DOI: 10.1108/arla-02-2019-0056
|View full text |Cite
|
Sign up to set email alerts
|

Ranking web as indicator of knowledge diffusion: an application for SMEs

Abstract: PurposeThe purpose of this article is to analyze the influence of the diversity of information and the use of Web 2.0 applications on the web positioning of online business information providers.Design/methodology/approachA total of 203 online business information provider websites were selected using three search engines (Google, Yahoo and Bing). This information was encoded to develop two logistic regression models.FindingsThe results suggest that the knowledge offered and the resources used to transfer this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 110 publications
(115 reference statements)
0
6
0
Order By: Relevance
“…According to these results, the firms that achieve these competencies will be able to innovate more easily and obtain better performance. Currently, however, firms have unlimited access to various types of information and knowledge (Gaviria-Marin and Cruz-Cázares 2020 ), which could imply a risk, as they do not have the capacity to discriminate based on the quality of the different information sources that are integrated into the firm. This could negatively affect decision making in SMEs (Habjan et al 2014 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…According to these results, the firms that achieve these competencies will be able to innovate more easily and obtain better performance. Currently, however, firms have unlimited access to various types of information and knowledge (Gaviria-Marin and Cruz-Cázares 2020 ), which could imply a risk, as they do not have the capacity to discriminate based on the quality of the different information sources that are integrated into the firm. This could negatively affect decision making in SMEs (Habjan et al 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has shown that SMEs do not take advantage of the full potential of ICT solutions as much as large firms do. During the last decade, technological progress has motivated small businesses to venture into the adoption of ICT (Gaviria-Marin and Cruz-Cázares 2020 ). However, these firms still need to implement/enhance capabilities to manage the technologies and achieve the desired effect on the business.…”
Section: Hypotheses Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Results of the moderating role of ICT in strengthening learning to provoke knowledge assimilation are also shown [5] with a positive relationship between KM and performance [4].…”
Section: Information and Communication Technologies And Knowledge Man...mentioning
confidence: 93%
“…Another problem identified in SMEs is the lack of investment and necessary training in ICT which represents an invaluable asset and an important resource that adds value to products and services [3] as well as the correct decisions made by firms. However, despite these barriers to the use of ICT in SMEs in the last decade, SMEs have been motivated to adopt ICT [4].…”
Section: Introductionmentioning
confidence: 99%